Aktualisasi Nilai-Nilai Pendidikan Islam Dalam Budaya Adiwiyata di Sekolah Menengah Pertama Negeri 1 Umbulsari Jember - Anas, Moh. Azwar; Chotib, Moh.; Muhith, Abd (IJIT: Indonesian Journal of Islamic Teaching, 2024)
ABSTRACT The character of environmental awareness regarding the preservation of the environment is a fundamental discussion for the sustainability of future generations. Therefore, efforts to preserve the environment can also be conducted through school education. This study aims to realize environmental awareness by understanding Islamic Educational Values focused on the environment, which aims to enhance environmentally friendly attitudes and behaviours. Environmentally-oriented formal education aspires to foster attitudes and behaviors among school members who are responsible for environmental preservation efforts through Islamic Education. Research Focus: 1) What are the Islamic Educational Values in the Adiwiyata Culture at SMP Negeri 1 Umbulsari Jember? 2) How is the Actualization of Islamic Educational Values in the Adiwiyata Culture at SMP Negeri 1 Umbulsari Jember? Research Objectives: 1) To analyze the Islamic Educational Values in the Adiwiyata Culture at SMP Negeri 1 Umbulsari Jember. 2) To analyze the Actualization of Islamic Educational Values in the Adiwiyata Culture at SMP Negeri 1 Umbulsari Jember. The research method uses a qualitative approach, specifically a case study. The research location is SMP Negeri 1 Umbulsari Jember. The presence of the researcher and the research subjects are determined using purposive sampling, and data collection includes interviews, observations, and documentation. Data analysis follows the theory of Matthew B. Milles, Huberman, and Saldana, using qualitative data analysis techniques, including data condensation, data presentation, and conclusion drawing. Data validity is ensured through source and technique triangulation.The conclusions of this research are: 1) The Islamic Educational Values in the Adiwiyata Culture at SMP Negeri 1 Umbulsari are initiated through school policies encompassing the school's vision, mission, goals, and the Adiwiyata cultural programs. This integration includes Islamic Education subjects who understand the environment from an Islamic perspective. 2)The Actualization of Islamic Educational Values in the Adiwiyata Culture at SMP Negeri 1 Umbulsari is demonstrated through waste recycling, Friday Devotion (Jum'at Taqwa), and environmental awareness posters. Keyword: Strategy, 3-5 kata kunci , kata kunci 1, kata kunci 2, dst